Pengaruh Layanan Penguasaan Konten dengan Teknik Modeling Simbolik terhadap Perilaku Prososial Mahasiswa - Anggitasari, Dyah Widhi; awalya, awalya (Universitas Negeri Semarang, 2016)
Based on introduction study has founded that prosocial behavior of student have a less category show with less helping behavior, emphaty, friendship, coorperation, dan care with other. The study purposed to improve prococial behavior through mastery of content services by symbolic modeling technique. This study is experimental study. This study was conducted at Guidance Counseling students as the sample with twenty five students. The data were collected by prosocial behavior scale. The data analysis technique used descriptive percentage analysis and wilcoxon analysis. The results of descriptive percentage showed that prosocial behavior of student before student are given mastery of content services by symbolic modeling technique is in the average middle category (67,37%) and after obtaining mastery of content services by symbolic modeling technique have an average in the high category (83,99%). Based on the wilcoxonthest showed that Zcount 0 and Ztable 257, so Zcount 0 < Ztable 2,57, then Ha is accepted an Ho is rejected. The result showed mastery of content services with symbolic modeling technique have a positif influence on prosocial behavior